Peripherally Induced Regulatory T Cells: Recruited Protectors of the Central Nervous System against Autoimmune Neuroinflammation - Jones, Andrew; Hawiger, Daniel (Frontiers in Immunology, 2017)
Defects in regulatory T cells (Treg cells) aggravate multiple sclerosis (MS) after its onset and the absence of Treg cell functions can also exacerbate the course of disease in an animal model of MS. However, autoimmune neuroinflammation in many MS models can be acutely provoked in healthy animals leading to an activation of encephalitogenic T cells despite the normal induction of immune tolerance in the thymus including thymically-produced (t)Treg cells. In contrast, neuroinflammation can be ameliorated or even completely prevented by the antigen-specific Treg cells formed extrathymically in the peripheral immune system (pTreg cells) during tolerogenic responses to relevant neuronal antigens. This review discusses the specific roles of regulatory T cells in blocking neuroinflammation, examines the impact of peripheral tolerance and dendritic cells on a relevant regulation of neuroinflammation and explores some of the most recent advances in elucidation of specific mechanisms of the conversion and function of pTreg cells including the roles of CD5 and Hopx in these processes